Electrical characteristics of Cu-doped In2O3/Sb-doped SnO2 ohmic contacts for high-performance GaN-based light-emitting diodes - Oh, Joon-Ho; Seong, Tae-Yeon; Hong, H. -G.; Kim, Kyoung-Kook; Yoon, S. -W.; Ahn, J. -P. (SPRINGER, 2011)
We characterized the electrical and chemical properties of Cu-doped In2O3(CIO) (2.5 nm thick)/Sb-doped SnO2(ATO) (250 nm thick) contacts to p-type GaN by means of current-voltage measurement, scanning transmission electron microscope (STEM) and x-ray photoemission spectroscopy (XPS). The CIO/ATO contacts show ohmic behaviors, when annealed at 530 and 630A degrees C. The effective Schottky barrier heights on diodes made with Ni (5 nm)/Au (5 nm) contacts decrease with increasing annealing temperature. STEM/energy dispersive x-ray (EDX) profiling results exhibit the formation of interfacial In-Ga-Sn-Cu-oxide. XPS results show a shift of the surface Fermi level toward the lower binding energy side upon annealing. Based on the STEM and XPS results, the ohmic formation mechanisms are described and discussed.
Keywords: TRANSPARENT CONDUCTING OXIDE; P-TYPE GAN; OPTICAL-PROPERTIES; FILMS; ELECTRODES; DEPOSITION; RESISTANCE; PRESSURE; DEVICES; OUTPUT